Expert System Mendiagnosis Penyakit Hewan Peliharaan Melalui Penerapan Teknik Case Based Reasoning - Dwi Kurniawati; Dahriansah Dahriansah; Akmal Nasution (STMIK Budi Darma, 2022)
Disease is a certain abnormal condition that negatively affects the structure or function of part or all of the body of a living being. Disease is not only found in humans, but also in animals especially pets which are known to be more susceptible to disease. This study explains that it is important to maintain the health of pets so that the health of their owners can also be maintained properly. The lack of knowledge of pet lovers causes delays in handling these pets. Another problem besides pet disease is the lack of veterinarians or veterinary clinics in the Asahan area. To help overcome these problems, a system was created that can determine diseases quickly in pets such as dogs, cats and rabbits using the Case Based Reasoning method. This Case Based Reasoning method is used to find the disease similarity value by looking at previous cases. From the weight calculation carried out in this case, the highest similarity value is Worms with a percentage of 92,3076%. So the recommended treatment solution for new cases entered by users with symptoms of intestinal worms is regular deworming and regular grooming at least once every 14-15 days.